FIGO good practice recommendations on progestogens for prevention of preterm delivery. Issue 1 (14th September 2021) - Shennan, Andrew; Suff, Natalie; Leigh Simpson, Joe; Jacobsson, Bo; Mol, Ben W.; Grobman, William A.; ,
Abstract: Women at high risk of preterm birth (either a previous spontaneous preterm birth and/or sonographic short cervix) with a singleton gestation should be offered daily vaginal progesterone or weekly 17‐OHPC treatment to prevent preterm birth. Benefit is most significant in those with prior history of preterm birth and a short cervix. For women with a previous spontaneous preterm birth and a cervix ≥30 mm the effectiveness of progesterone is uncertain. In asymptomatic women with no prior history of previous preterm birth, no mid‐trimester loss, or no short cervical length, progesterone therapy is not recommended for the prevention of preterm birth. For those with unselected multiple pregnancies, progesterone therapy is not recommended for the prevention of preterm birth. Daily vaginal progesterone or weekly 17‐OHPC treatment can be used for the prevention of preterm birth. The preparation used should be decided by the woman and her clinician. There is no evidence of neurological or developmental benefit or harm in babies whose mothers use progestogens for preterm birth prevention antenatally. Synopsis: Women at high risk of preterm birth with a singleton gestation should be offered daily vaginal progesterone or weekly 17‐OHPC treatment to prevent preterm birth.